2019
DOI: 10.3389/fimmu.2019.00765
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Normothermic Machine Perfusion Conditions on Mesenchymal Stromal Cells

Abstract: Ex-situ normothermic machine perfusion (NMP) of transplant kidneys allows assessment of kidney quality and targeted intervention to initiate repair processes prior to transplantation. Mesenchymal stromal cells (MSC) have been shown to possess the capacity to stimulate kidney repair. Therefore, the combination of NMP and MSC therapy offers potential to repair transplant kidneys. It is however unknown how NMP conditions affect MSC. In this study the effect of NMP perfusion fluid on survival, metabolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 46 publications
1
31
0
Order By: Relevance
“…Third, conformational B-cell epitopes were predicted with DiscoTope2 on molecular structures of SARS-CoV-2 proteins 8 . The unprecedented speed at which experimental SARS-CoV-2 structures have been solved and deposited in the PDB allowed us to predict epitopes on 13 proteins (Table S3 ) 9 12 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, conformational B-cell epitopes were predicted with DiscoTope2 on molecular structures of SARS-CoV-2 proteins 8 . The unprecedented speed at which experimental SARS-CoV-2 structures have been solved and deposited in the PDB allowed us to predict epitopes on 13 proteins (Table S3 ) 9 12 .…”
Section: Resultsmentioning
confidence: 99%
“…Current in-silico predictions suffer from sensitivity issues and this will only improve with larger training sets, i.e. more experimental structures of antigen–antibody complexes 8 . Nonetheless, our combined predictions accurately ranked the spike RBD and N-term nucleoprotein as top choice candidates for specific SARS-CoV-2 diagnostics, which was subsequently confirmed by ELISA serological tests.…”
Section: Resultsmentioning
confidence: 99%
“…Gregorini et al demonstrated that delivering MSCs during hypothermic machine perfusion improved outcomes in a rat model of ischemic kidney injury (107). Recently, Sierra Parraga et al demonstrated that machine perfusion of MSCs supports their function and survival, although more work will be required to determine the optimal conditions for perfusion (108). Notably, these strategies may reduce the need for immunosuppression to prevent organ rejection (109).…”
Section: Routes Of Therapeutic Cell Deliverymentioning
confidence: 99%
“…The effect of kidney NMP perfusion fluid constituents on the viability of MSC has been investigated. This study stimulated thawed and fresh MSC with perfusate and demonstrated MSC behaviour can be adversely affected by the conditions of the perfusion fluid [30]. Data showed that thawed MSCs have reduced viability in perfusion fluid, with reduced adherence to endothelial cells when compared with fresh MSCs.…”
Section: Cell Therapy In Kidney Machine Perfusionmentioning
confidence: 99%